Antibody neutralization and viral virulence in recurring dengue virus type 2 outbreaks - Wong, S.S.; Abd-Jamil, J.; AbuBakar, Sazaly (2007)
Outbreaks involving dengue viruses (DENV) of the same genotype occur in a cyclical pattern in Malaysia. Two cycles of outbreaks involving dengue virus type 2 (DENV-2) of the same genotype occurred in the 1990s in the Klang Valley, Malaysia. Sera of patients from the first outbreak and sera of mice inoculated with virus from the same outbreak had poorer neutralization activity against virus of the second outbreak. Conversely, patient sera from the second outbreak showed higher neutralization titer against virus of the early outbreak. At subneutralizing concentrations, sera of mice immunized with second outbreak virus did not significantly enhance infection with viruses from the earlier outbreak. Amino acid substitution from valine to isoleucine at position 129 of the envelope protein ( E), as well as threonine to alanine at position 117 and lysine to arginine at position 272 of the NS1 protein, differentiated viruses of the two outbreaks. These findings highlight the potential influence of specific intragenotypic variations in eliciting varied host immune responses against the different DENV subgenotypes. This could be an important contributing factor in the recurring homogenotypic dengue virus outbreaks seen in dengue-endemic regions.